Spark ignition vehicle contributions to atmospheric fine elemental carbon concentrations in coastal, rural and urban communities using polycyclic aromatic hydrocarbon tracers in the CMB model modified for reactivity - Eiguren-Fernandez,Arantzazu (2009)
We apportioned the elemental carbon (EC) component of ambient PM2.5 attributable to emissions from spark ignition (SI) vehicles in samples collected over a three-year period in twelve Southern California communities, including coastal, rural, and urban areas using the chemical mass balance model (CMB8) modified for polycyclic aromatic hydrocarbon (PAH) reactivity. Selected PAH/EC ratios, measured in samples collected in the Caldecott tunnel were evaluated for use as fingerprints. PAH reactivity which occurs during atmospheric transport and affects the source contribution estimates during the summer/fall/spring months was accounted for using experimentally measured decay constants. Results showed that benzo[ghi]perylene and indeno[1,2,3-cd]pyrene can be used successfully as specific tracers of EC contributions from SI vehicles. The average EC portion of PM2.5 attributed by the model to SI emissions at these communities was 39, 58 and 62%, respectively, during the summer, spring/autumn, and winter. For all seasons, coastal community contributions represent about twice those found in the rural and urban inland communities, before December 2003 when MTBE was still in use in California.